2013
DOI: 10.2105/ajph.2013.301337
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Price Elasticities to Inform Public Health Research and Intervention Studies: Key Issues

Abstract: Pricing policies such as taxes and subsidies are important tools in preventing and controlling a range of threats to public health. This is particularly so in tobacco and alcohol control efforts and efforts to change dietary patterns and physical activity levels as a means of addressing increases in noncommunicable diseases. To understand the potential impact of pricing policies, it is critical to understand the nature of price elasticities for consumer products. For example, price elasticities are key paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 37 publications
0
49
0
2
Order By: Relevance
“…We lack price data for eating at non-fast food restaurants and thus could not further evaluate these pricing dynamics. Accounting for cross-price elasticities (the impact of a specific food price on the consumption of other foods) is a pervasive challenge in food price-demand studies 42 . Limitations of our data did not allow us to better delineate price-consumption dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…We lack price data for eating at non-fast food restaurants and thus could not further evaluate these pricing dynamics. Accounting for cross-price elasticities (the impact of a specific food price on the consumption of other foods) is a pervasive challenge in food price-demand studies 42 . Limitations of our data did not allow us to better delineate price-consumption dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Taxation or other price-based policies may also be more effective among those who consume excessive amounts of sugar (21) . For example, a study by Gustavsen in Norway found that tax-induced price increases in soft drinks could reduce consumption by more than twice as much among high consumers as among those who consumed the lowest amounts (22) .…”
Section: Interventions Targeting High Sugar Consumersmentioning
confidence: 99%
“…For example, how much does a tax on one food affect consumption of other foods? PE are commonly used to convert a food tax/subsidy intervention to a change in total diet [19] which is then linked to changes in BMI and other risk factors, then disease rates, and then to morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%